Impaired hepatic glycogen synthesis in glucokinase-deficient (MODY-2) subjects - Velho, G; Petersen, K F; Perseghin, G; Hwang, J H; Rothman, D L; Pueyo, M E; Cline, G W; Froguel, P; Shulman, G I (The Journal of clinical investigation, 1996)
All glucokinase gene mutations identified to date have been localized to exons that are common to the pancreatic and hepatic isoforms of the enzyme. While impaired insulin secretion has been observed in glucokinase-deficient subjects the consequences of this mutation on hepatic glucose metabolism remain unknown. To examine this question hepatic glycogen concentration was measured in seven glucokinase-deficient subjects with normal glycosylated hemoglobin and 12 control subjects using 13C nuclear magnetic spectroscopy during a day in which three isocaloric mixed meals were ingested. The relative fluxes of the direct and indirect pathways of hepatic glycogen synthesis were also assessed using [1-13C]glucose in combination with acetaminophen to noninvasively sample the hepatic UDP-glucose pool. Average fasting hepatic glycogen content was similar in glucokinase-deficient and control subjects (279+/-20 vs 284+/-14 mM; mean+/-SEM), and increased in both groups after the meals with a continuous pattern throughout the day. However, the net increment in hepatic glycogen content after each meal was 30-60% lower in glucokinase-deficient than in the control subjects (breakfast, 46% lower, P < 0.02; lunch, 62% lower, P = 0.002; dinner; 30% lower, P = 0.04). The net increment over basal values 4 h after dinner was 105 +/-18 mM in glucokinase-deficient and 148+/-11 mM in control subjects (P = 0.04). In the 4 h after breakfast, flux through the gluconeogenic pathway relative to the direct pathway of hepatic glycogen synthesis was higher in glucokinase-deficient than in control subjects (50+/-2% vs 34+/-5%; P = 0.038). In conclusion glucokinase-deficient subjects have decreased net accumulation of hepatic glycogen and relatively augmented hepatic gluconeogenesis after meals. These results suggest that in addition to the altered beta cell function, abnormalities in liver glycogen metabolism play an important role in the pathogenesis of hyperglycemia in patients with glucokinase-deficient maturity onset diabetes of young.